1999
DOI: 10.1353/aad.2012.0337
|View full text |Cite
|
Sign up to set email alerts
|

Coteaching Deaf and Hearing Students: Research on Social Integration

Abstract: C oteaching , also known as team teaching , offers an alternative to the dilemma of choosing between the residential school, which offers a deaf community but sometimes a poor record of achievement, and inclusion, which promises better achievement but results in increased social isolation. Under a coteaching arrangement, deaf or hard of hearing students can share a deaf peer group while being exposed to the social contact and academic requirements of a mainstream class. The study sample consists of the deaf or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
3
17
1
3
Order By: Relevance
“…This is similar to the findings regarding attitude improvement of nondisabled students toward students with disabilities (e.g. Stager and Young, 1981), and those regarding positive attitudes or acceptance of D/HH students by their hearing peers in inclusion programmes (Kluwin, 1999;Kluwin et al, 2002;Luckner, 1999;Power and Hyde, 2002;Powers, 1996). The findings in this study suggest that setting may have contributed to the hearing subjects' positive attitudes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to the findings regarding attitude improvement of nondisabled students toward students with disabilities (e.g. Stager and Young, 1981), and those regarding positive attitudes or acceptance of D/HH students by their hearing peers in inclusion programmes (Kluwin, 1999;Kluwin et al, 2002;Luckner, 1999;Power and Hyde, 2002;Powers, 1996). The findings in this study suggest that setting may have contributed to the hearing subjects' positive attitudes.…”
Section: Discussionsupporting
confidence: 87%
“…8(2): 62-74 (2006) Published online in Wiley InterScience (www.interscience.wiley.com) DOI: 10.1002/dei.190 A review of the literature indicates that most, but not all, studies support the positive aspects of inclusion mentioned above. That is, studies have reported satisfactory outcomes for academic progress and social development of D/HH students, including positive attitudes toward and acceptance of D/HH students by their hearing peers (Kluwin, 1999;Kluwin and Stinson, 1993;Kluwin et al, 2002;Luckner, 1999;Power and Hyde, 2002;Powers, 1996). On the other hand, a few studies have reported that D/HH students have encountered negative attitudes held by their hearing peers, have experienced isolation, or loneliness, or have failed to establish close relationships with their hearing peers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a team-taught kindergarten classroom that fully included children with hearing loss found no difference on measures of popularity (Kluwin & Gonsher, 1994) between the children based on hearing status. Kluwin (1999) reported no difference in loneliness between deaf and hearing students in an integrated classroom. Social relationships appear to develop more effectively with more plentiful opportunities to interact with both deaf and hearing peers, and with teacher facilitation and support for interaction (Mertens, 1989;.…”
Section: The Social Consequences Of Inclusionmentioning
confidence: 93%
“…In particular, they need to be able to collaborate with a variety of support professionals including speech-language pathologists, audiologists, occupational therapists, physical therapists, and general education teachers (Kluwin, 1999;.…”
Section: Dh9s1: Increase Proficiency and Sustain A Life-long Commitmementioning
confidence: 99%